Peran Kepemimpinan dalam IT Governance terhadap Keberhasilan Praktik dalam Organisasi - Kendrik Jonatan; Suryo Pramono Liegestu; Frenkie Tan; Carlos Justin Khomali; Erwin Geovanis Gultom; Avaleska Avaleska (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
In today's increasingly competitive business environment driven by technological advances, companies are required to implement effective strategies to remain in existence. Technology plays a key role, driving widespread adoption across various business functions. One of these strategies is IT governance, which aims to optimize IT management and investment results. This research explores the important role of executive leadership in shaping and sustaining IT governance practices in organizations. It emphasizes alignment of IT objectives with overall corporate objectives, along with risk management considerations. Additionally, it draws a correlation between humanitarian organizations' initiatives and IT governance maturity, the importance of proactive leadership. Through the lens of the literature, this study investigates the impact of executive leadership on the implementation and success of IT governance, providing an in-depth understanding of the key factors that influence organizational effectiveness.